OFR-120-85 Retrofit Noise Control Of Underground Load-Haul-Dump Machines (The National Institute for Occupational Safety and Health (NIOSH), 1984)
This report summarizes the work performed under USBM Contract No. H0395041. The primary objective of this work was to extend the noise control technology developed under earlier USBM projects to a wider range of load-haul-dump models to evaluate the general applicability of these techniques. Noise control treatments were designed, fabricated, and installed on three Wagner LHDs (an 5T-2B, ST-2D, and an 5T-8A) selected as demonstration machines for this project. The machines were evaluated either in production mines or at the Bureau's Lake Lynn Mine. The results indicate that it is possible to achieve overall noise reductions of between 4 and 8 dB using these techniques. Engine cooling and seal design were determined to be important design issues in such treatments.